Stem Cells and Cellular Origins of Breast Cancer: Updates in the Rationale, Controversies, and Therapeutic Implications - Zhou, Jiaojiao; Chen, Qishan; Zou, Yiheng; Chen, Huihui; Qi, Lina; Chen, Yiding (Frontiers in Oncology, 2019)
Breast cancer stem cells have been known to contribute immensely to the carcinogenesis of the breast and therapeutic resistance in the clinic. Current studies show that the population of breast cancer stem cells is heterogeneous, involving various cellular markers and regulatory signaling pathways. In addition, different subtypes of breast cancer exhibit distinct subtypes and frequencies of breast cancer stem cells. In this review, we provide an overview of the characteristics of breast cancer stem cells, including their various molecular markers, prominent regulatory signaling, and complex microenvironment. The cellular origins of breast cancer are discussed to understand the heterogeneity and diverse differentiations of stem cells. Importantly, we also outline the recent advances and controversies in the therapeutic implications of breast cancer stem cells in different subtypes of breast cancer.